Modern Applications of Biotechnology in Monitoring Environmental Pollutants and their Impact on Human Health - Habib, Ali Falah Hassan; Hamid, Murtadha Hamza; Khazal, Hijran Mushtaq Talib; Dohan, Nour Hassan; Idan, Zahraa Mustafa (American Journal of Botany and Bioengineering, 2025)
The extensive release of industrial and agricultural wastes resulting in environmental pollution causes a range of toxic effects in living organisms. A major issue today is the presence of multiple pollutants in the environment such as heavy metals, pesticides, industrial chemicals, plastics, detergents, and other xenobiotics entering the body through ingestion, inhalation, and skin adsorption. The adverse effects on human and wildlife health are indisputable. Genomic DNA is a sensitive target for damaged cells and thus for mutagenic and carcinogenic agents, which constitute a serious public hazard. These types of pollutants are found in all environmental compartments, including water, air, and soil. Several physical, chemical, and biological techniques have been developed to alleviate environmental pollution; many of them are hazardous, time-consuming, and costly. Modern biotechnological tools include gene probes and specifically designed biosensors for monitoring environmental pollutants. An alternative is the use of genetically engineered microbial, plant, and animal biosensors for rapid, simple, cost-effective, and on-site biosensing of specific biologically important pollutants. Recent advances in recombinant DNA technology, especially in the construction and use of recombinant microbial, plant, and animal biosensors to monitor water-, soil-, and air-borne pollutants at low concentrations, are discussed from an environmental health perspective. Biotechnology is the exploitation of biological processes for development and use in manufacturing, service industries, agriculture, food science, and medicine. Environmental health deals with the physical, chemical, and biological factors affecting humans.